(viii) 4x-2x2-3x2+x
![4 {x}^{2} - 2 {x}^{2} - 3 {x}^{2} + {x}^{2} 4 {x}^{2} - 2 {x}^{2} - 3 {x}^{2} + {x}^{2}](https://tex.z-dn.net/?f=4+%7Bx%7D%5E%7B2%7D++-+2+%7Bx%7D%5E%7B2%7D++-+3+%7Bx%7D%5E%7B2%7D++%2B++%7Bx%7D%5E%7B2%7D+)
Answers
Answered by
2
Answer:
0
Step-by-step explanation:
4 - 2
- 3
+
= (4 -2
) - (3
+
)
= 2 - 2
= 0
= 0
Please mark me brailiest!!
Answered by
30
Explanation:
We get 0 .
Alternatively method :
Taking 2x square common &x square:
Learn more :
- Above equation is in the form of Binomial polynomial,as it having the highest power 2.
Similar questions
English,
3 months ago
Math,
3 months ago
Math,
7 months ago
Computer Science,
7 months ago
Physics,
1 year ago